Pharmacokinetics/pharmacodynamics of gamithromycin for treating Pasteurella multocida infection in cattle using a tissue cage model. - Qingwen Yang; Xuesong Liu; Yongzhi Lv; Yushen Li (PLoS ONE)
In this study, gamithromycin, a long-acting azalide antibiotic recently introduced for bovine respiratory disease (BRD) treatment, was evaluated for its effectiveness against Pasteurella multocida using a cattle tissue cage model. Gamithromycin (6 mg/kg) was administered via both intravenous and subcutaneous routes and the gamithromycin contents in sera, transudates, and exudates were measured using HPLC/MS-MS. Non-compartmental methods were utilized for assessing pharmacokinetic parameters and an inhibitory sigmoid Emax model determined associations between the pharmacokinetic/pharmacodynamic (PK/PD) indices and antibacterial activity. The area under the 24-h concentration-time curve/minimum inhibitory concentration (AUC0-24h/MIC) was found to be an optimal measure of antibacterial activity. The AUC0-24h/MIC values over 24 h in sera, transudates, and exudates were 0.27, 0.17, and 0.14, respectively, for bacteriostatic effects, while for bactericidal activity, the AUC0-24h/MIC values over 24 h in sera and exudates 3.76 and 5.31, respectively, and for bacterial eradication, the serum value was 18.46. These findings contribute valuable insights into the optimization of gamithromycin dosing regimens for treating respiratory conditions caused by Pasteurella multocida in cattle.